2019
DOI: 10.3390/toxins11080481
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of the Mycotoxin Zearalenone to its Metabolites Hydrolyzed Zearalenone (HZEN) and Decarboxylated Hydrolyzed Zearalenone (DHZEN) Diminishes its Estrogenicity In Vitro and In Vivo

Abstract: Zearalenone (ZEN)-degrading enzymes are a promising strategy to counteract the negative effects of this mycotoxin in livestock. The reaction products of such enzymes need to be thoroughly characterized before technological application as a feed additive can be envisaged. Here, we evaluated the estrogenic activity of the metabolites hydrolyzed zearalenone (HZEN) and decarboxylated hydrolyzed zearalenone (DHZEN) formed by hydrolysis of ZEN by the zearalenone-lactonase Zhd101p. ZEN, HZEN, and DHZEN were tested in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 72 publications
(129 reference statements)
0
43
0
Order By: Relevance
“…In addition, ZEN (33) was converted to hydrolyzed ZEN (155) through hydrolysis, and then to decarboxylated hydrolyzed ZEN (156) through spontaneous decarboxylation by Bacillus pumilus ( Figure S84) [122]. Similar biotransformation of ZEN (33) was also observed by using a lactonase named ZHD101 from Clonostachys rosea [123,124].…”
Section: Miscellaneous Reactionsmentioning
confidence: 58%
See 2 more Smart Citations
“…In addition, ZEN (33) was converted to hydrolyzed ZEN (155) through hydrolysis, and then to decarboxylated hydrolyzed ZEN (156) through spontaneous decarboxylation by Bacillus pumilus ( Figure S84) [122]. Similar biotransformation of ZEN (33) was also observed by using a lactonase named ZHD101 from Clonostachys rosea [123,124].…”
Section: Miscellaneous Reactionsmentioning
confidence: 58%
“…T-2 toxin (31) HT-2 toxin (122) Eubacterium BBSH 797 (bacterium) [86] HT-2 toxin (122),15-acetyl-tetraol (123),T-2 tetraol (124) Liver and intestines of rats [102] Neosolaniol ( Bacillus amyloliquefaciens (bacterium) [98] Lactone-opened ochratoxin A (OP-OTA, 120) Rats [99] Ochratoxin C (OTC) = Ochratoxin A ethyl ester (121) Ochratoxin A (OTA, 21)…”
Section: Rats [100]mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the lactonohydrolase ZHD101 from C. rosea catalyzing this reaction was characterized and its encoding gene was found and cloned [23]. Further, the reaction mechanism was also unveiled [24] and the structures of degradation products were confirmed as well, which were followed by evaluation on the toxicity of these products ( Figure 1) including hydrolyzed ZEN (HZEN) and decarboxylated hydrolyzed ZEN (DHZEN) [25].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to enzymatic detoxification, Alberts et al [10] developed an innovative method using the commercial fumonisin esterase FumD to reduce fumonisin B in whole maize, resulting in the formation of the hydrolyzed breakdown product, HFB1, associated with the aqueous phase to be discarded. Fruhauf et al [11] concluded that the cleavage of ZEA by the zearalenone-lactonase Zhd101p reduces its estrogenicity in piglets, providing an important basis for the further evaluation of ZEA-degrading enzymes.…”
mentioning
confidence: 99%